Application of appropriate technology for making hand sanitizer with Citronella Oil - Dante Alighiri; Sigit Priatmoko; Samuel Budi Wardhana Kusuma; Sri Nurini; Eko Budi Susatyo (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The vision of the orphanage is to create a society that is physically and mentally prosperous through empowering underprivileged children, progressively and professionally to form a generation of Khaira Ummah. To support this, the community service team needs to equip the orphanage children with knowledge and skills that are expected to provide creative ideas in entrepreneurship through the application of appropriate technology for the production of hand sanitizer from citronella oil. The resulting hand sanitizer has two functions as a natural hand antiseptic and mosquito repellent. The stages of this community service activity had been carried out by the methods of lectures, discussions, demonstrations, and practices. After the activities were completed, assistance and evaluation of activities were carried out. Almost all participants had been a level of understanding of all community service activities ( 90%) which included knowledge, skills, perception, and motivation. The evaluation of the activities had been carried out by 95s of participants, satisfied with this community service activity. This community Service activity had been succeeded in equipping the orphanage children and supporting the vision of the orphanage of Khaira Ummah.